Toward a framework of effective professional development for primary schools in Ho Chi Minh City, in Vietnam - Nguyen, Thi Phuong Linh (Animo Repository, 2015)
This study identifies teachers perceptions of the which they have participated in over the last two years. It explores how they perceive their developmental needs as being met along with their views of the availability of the professional development and the essential components of professional development for teachers in general. This has been done in order to help develop a framework for effective professional development for primary schools in Ho Chi Minh City, Vietnam. The study employed a multiple case design which involved four participating teachers, one each from four primary schools in Ho Chi Minh City. Results of the study reveal that professional development opportunities were available as perceived by the participants and that they appreciated the usefulness of the provided training courses, the schools support, opportunities to voice their teaching concerns and the provision of interactive learning in the workplace. Furthermore, the expectation of having access to better training courses was expressed as the participating teachers who found barriers in provided training courses in terms of content, delivery mode, personality and culture, personal concerns, course duration and barriers to implementation of alternative teaching methods. The essential components of effective professional development identified include provision of pre and post training strategies, quality human resources service, school support, teachers attitudes toward professional development, relevant course content, opportunities for reactive learning, equitable opportunity for professional development and appropriate length of training courses.